How Did the 2003 SARS Epidemic Shape Chinese Trade? - Ana P. Fernandes; Heiwai Tang (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper examines the impact of the Severe Acute Respiratory Syndrome (SARS) epidemic on China's trade. Using quarterly transaction-level trade data of all Chinese firms, we find that firms in regions with local transmission of SARS experienced lower import and export growth at both the intensive and extensive margins, compared to those in the unaffected regions. The affected firms' trade growth remained lower two years after SARS. Products that are more capital-intensive, skill-intensive, upstream in the supply chains, and differentiated experienced a smaller export decline but a stronger recovery. Small exporters were more likely to exit, slowing down trade recovery.
Keywords: F12; F14; 330; Covid-19; SARS; trade collapse; post-pandemic recovery; natural disasters; disruption; global supply chains